2016
DOI: 10.1097/sla.0000000000001863
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional Recurrence After Sentinel Lymph Node Dissection With or Without Axillary Dissection in Patients With Sentinel Lymph Node Metastases

Abstract: Background and Objective The early results of the American College of Surgeons Oncology Group (ACOSOG) Z0011 trial demonstrated no difference in locoregional recurrence for patients with positive sentinel lymph nodes (SLN) randomized either to axillary lymph node dissection (ALND) or SLN dissection (SLND) alone. We now report long-term locoregional recurrence results. Methods ACOSOG Z0011 prospectively examined overall survival of patients with SLN metastases undergoing breast-conserving therapy randomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
298
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 486 publications
(318 citation statements)
references
References 25 publications
12
298
1
7
Order By: Relevance
“…Z0011 study showed that patients with T1/T2 lesion and negative axillary lymph nodes and with up to two positive SL, referred to adjuvant systemic therapy, did no benefit from axillary surgery, even with 27% of residual disease in the SL arm. These patients had the same survival free of the disease, same mortality and lower morbidity (edema, numbness of arm and quality of life) when compared to patients submitted to axillary surgery 9 . In our study, reinforcing the results of Z0011, T staging, T1/T2 versus T3/T4 could help decide which women should be submitted to further axillary surgery.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Z0011 study showed that patients with T1/T2 lesion and negative axillary lymph nodes and with up to two positive SL, referred to adjuvant systemic therapy, did no benefit from axillary surgery, even with 27% of residual disease in the SL arm. These patients had the same survival free of the disease, same mortality and lower morbidity (edema, numbness of arm and quality of life) when compared to patients submitted to axillary surgery 9 . In our study, reinforcing the results of Z0011, T staging, T1/T2 versus T3/T4 could help decide which women should be submitted to further axillary surgery.…”
Section: Discussionmentioning
confidence: 89%
“…ACOSOG Z0011 work evaluated, in a randomized manner, 891 patients submitted to AL or only follow up after positive SLB. There was no statistical difference between loco-regional and distant relapse rates in both groups 9 . The objective of this study was to verify the existence of association among several studied variables and the axillary lymph node involvement in patients with breast cancer with positive SLB.…”
mentioning
confidence: 85%
“…And, most breast surgeons do not perform axillary lymph node dissection even in the presence of 1 or two positive sentinel lymph node(s) due to the results of ACOSOG Z0011 trial (19). New consensus conferences on surgical margins in patients with invasive and ductal carcinoma in situ (DCIS) recommend no-ink on tumour for invasive, and 2 mm for DCIS as clear surgical margin (20)(21).…”
Section: Personalized Surgerymentioning
confidence: 99%
“…The population studied with mainly ER positive disease (more than 80% of whom would be expected to be Her2 negative) has, often, even in the metastatic setting, a more indolent course (not unusually with bone only disease) and thus OS at 6 years may be too short for definite conclusions when studying localized disease. Moreover, and at closer scrutiny, local recurrence rates display some discernible differences between the two groups in Z0011 [22] . The ALND group had numerically more (3.6% vs 1.9% in the SLN group) in-breast recurrences.…”
Section: Introductionmentioning
confidence: 99%